2017
DOI: 10.1515/frp-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Forest management and hunting in areas adjacent to national parks: the example of the Magura National Park

Abstract: Abstract. the aim of the study was to evaluate arguments for hunting and its impact on forest management and conservation in national parks as well as areas directly adjacent to them. the issue was examined using the example of the Magura national Park (MnP) for which data on the number of deer and predatory mammals included in the statistical yearbooks for 2013-2014 were available. the quality and size of the food sources provided by this type of forest habitat were evaluated using data obtained from the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A new assessment of environmental capacity should be conducted, considering the biomass of the forest vegetation cover. In this manner, the admissible levels of cervid densities in forests may be more realistic (Wajdzik et al 2015). The described method of large-area inventory of cervids makes this task real by enabling verification of their density in forests with different food abundance.…”
Section: Discussionmentioning
confidence: 99%
“…A new assessment of environmental capacity should be conducted, considering the biomass of the forest vegetation cover. In this manner, the admissible levels of cervid densities in forests may be more realistic (Wajdzik et al 2015). The described method of large-area inventory of cervids makes this task real by enabling verification of their density in forests with different food abundance.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that culling was intensified in this park in the year the park was established, and it continued for many years at a higher level than before the park's creation (Hędrzak 2018). According to Wajdzik et al (2017), the population density of the ungulates in the park threatens biodiversity, and the large number of predators is not sufficient to limit the increase in deer numbers. The authors found that the deer migrating from the park could cause damage in a commercial forest as far away as 100 km from its borders, and assumed that the deer would move along the green corridors through the forests in hunting districts 233 and 234.…”
Section: Discussionmentioning
confidence: 99%
“…Our models for MNP show that reducing the number of deer in these hunting districts has no significance for regulating the numbers of deer in the park. However, since the increase in damage in the Gorlice and Łosie Forestry Districts mentioned by Wajdzik et al (2017) arises from the high density of deer in Magurski NP, limiting the damage could be achieved by increasing the culling of hinds in the districts situated east of the park, especially in district No. 197, which cuts into the area being protected (see map in Figure 1).…”
Section: Discussionmentioning
confidence: 99%